The UPC2 gene in Kluyveromyces lactis stress adaptation - Betinova, Veronika; Toth Hervay, Nora; Elias, Daniel; Horvathova, Agnes; Gbelska, Yvetta (Folia microbiologica, 2022)
KlUpc2p, a transcription factor belonging to the fungal binuclear cluster family, is an important regulator of ergosterol biosynthesis and azole drug resistance in Kluyveromyces lactis. In this work, we show that the absence of KlUpc2p generates Rag- phenotype and modulates the K. lactis susceptibility to oxidants and calcofuor white. The KlUPC2 deletion leads to increased expression of KlMGA2 gene, encoding an important regulator of hypoxic and lipid biosynthetic genes in K. lactis and also KlHOG1 gene. The absence of KlUpc2p does not lead to statistically significant changes in glycerol, corroborating the expression of KlGPD1 gene, encoding NAD+-dependent glycerol-3-phosphate dehydrogenase, that is similar in both the deletion mutant and the parental wild-type strain. Increased sensitivity of Klupc2 mutant cells to brefeldin A accompanied with significant increase in KlARF2 gene expression point to the involvement of KlUpc2p in intracellular signaling. Our observations highlight the connections between ergosterol and fatty acid metabolism to modulate membrane properties and point to the possible involvement of KlUpc2p in K. lactis oxidative stress response.
Keywords: regulace genové exprese u hub; ergosterol; Ergosterol; fungální proteiny; transkripční faktory; Fungal Proteins; Kluyveromyces; Transcription Factors; delece genu; Gene Deletion; Gene Expression Regulation, Fungal